Gender’s role in students’ comprehension and achievement in Bahasa Indonesia subject at SDN Percontohan Medan - Rambe, Kartina Rahmadhani; Agustina, Widya (Jurnal Anifa: Studi Gender dan Anak, 2024)
Gender roles are social instructions that attempt to differentiate the physical functions of men and women. The study aims to determine the role of gender in students' understanding and achievement in Bahasa Indonesian subjects. It was conducted at SDN Experiment Medan in 2024. The populations in this study were students in classes IV B and IV C of SDN Experiment Medan, totaling 107 students who were students in the fourth grade at SDN Experiment Medan in 2024. Sampling was used using the cluster random sampling technique, where samples are taken by randomly taking classes from the population and selecting the sample using the Slovin formula with 35 respondents. This type of research is quantitative, and the primary and secondary data is obtained through documentation studies and a list of questions using a Likert scale. The data was processed statistically using the SPSS 26 program, namely the T-test, F-test and determinant coefficient models. The research results show that gender roles, understanding and achievement influence Indonesian language learning outcomes and increase awareness and implementation of gender equality. Hopefully, it can contribute to developing curricula and education policies that are more inclusive and gender equal.